A heavy fraction oil hydrotreating catalyst and preparation method thereof

By using weak acids or alkaline metal solutions during the preparation of hydrogenation catalysts, and using step-grading complex complex technology to solve the problem of catalyst and loss than the surface area of ​​the existing technology, to achieve higher perforated holes Ronghe ratio surface area is suitable for heavy oil hydrogenation processing process.

CN116408112BActive Publication Date: 2025-01-24PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111644501.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-01-24
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

During the preparation process, the use of acidic or alkaline solutions leads to loss of pore volume and specific surface area of ​​the alumina powder, affecting the performance of the catalyst.

Method used

Using weak acids or alkaline metal solutions, through step-grading complex complex technology, adjust the pH value of the solution, maximize the original hole structure of alumina alumina, and improve the metal concentration and decentralization effect of the active component.

Benefits of technology

The prepared hydrogenation treatment catalyst has a larger pores and comparison surface area, and the pore diameter distribution is concentrated. It is suitable for the hydrogenation process of heavy oil fixed bed, which improves the hydrogenation activity of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003443234810000092
    Figure BDA0003443234810000092
  • Figure BDA0003443234810000101
    Figure BDA0003443234810000101
Patent Text Reader

Abstract

The present invention discloses a heavy fraction oil hydroprocessing catalyst and a preparation method thereof. The preparation method comprises: adding an extrusion aid to pseudo-boehmite, kneading to obtain system 1; dissolving metal salts and / or metal oxides of active components and the aid in water to prepare solution A with a pH of 6.5 to 7.5; dividing the solution A into solution B and solution C for standby use; adding a complexing agent to the solution C to obtain solution D; adding the solution B to the system 1, kneading until the pseudo-boehmite is completely infiltrated, and obtaining a precursor E; adding the solution D to the precursor E, kneading, forming, drying, and calcining to obtain the catalyst. The hydroprocessing catalyst prepared by the present invention has a larger pore volume and specific surface area, and a concentrated pore size distribution, and is particularly suitable for a heavy oil fixed bed hydroprocessing process. The preparation method of the hydrogenation catalyst has the characteristics of simple process and low energy consumption, and is suitable for large-scale promotion and production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petrochemical industry, and in particular to a heavy fraction oil hydroprocessing catalyst and a preparation method thereof. Background Art

[0002] As the trend of heavy and inferior crude oil continues to intensify, the proportion of inferior heavy oil in refinery processing raw materials has increased year by year, and the output of heavy distillates such as vacuum gas oil (VGO), coker gas oil (CGO) and deasphalted oil (DAO) has also increased. Heavy distillates are mainly used as raw materials for subsequent secondary processing. The increase in the content of impurities such as sulfur, nitrogen, metals, and residual carbon will inevitably affect the quality of the product. Therefore, hydrogenation pretreatment of the above raw materials is an effective and important way. The core of this technology is the hydrogenation catalyst. The hydrogenation process of heavy distillates requires that the catalyst should have the characteristics of large pore volume, high specific surface area, and large pore size with concentrated pore distribution.

[0003] At present, the preparation methods of supported hydrogenation catalysts mainly include: impregnation method, kneading method, mixing-impregnation method, etc. Among them, the kneading method greatly reduces the preparation cost of the catalyst due to its short process flow and low energy consumption; the hydrogenation catalyst product prepared by this method has a high degree of pore structure preservation, large pore volume and high specific surface area, and is particularly suitable for the field of heavy and residual oil hydrogenation.

[0004] Patent application US4443558A adopts a complete kneading method to replace the "impregnation method" or "mixing-impregnation method" to prepare a supported hydrogenation catalyst in one step, which reduces the preparation cost by shortening the preparation process. However, the preparation of the catalyst adopts a method of adding acid first and then adding alkali. In this method, the pore volume and specific surface area of ​​the alumina powder are seriously lost due to the strong reaction of the strong acid added first with alumina, which destroys its original pore structure and makes the performance of the final catalyst unsatisfactory.

[0005] Patent application CN100340638C relates to a method for preparing a hydrocarbon hydroprocessing catalyst. The catalyst is γ-Al 2 O 3As a carrier, group VIB and group VIII metals are active components, and Ti and the like are active auxiliary agents. The catalyst auxiliary Ti of the invention is introduced by dripping titanium salt solution and the like during the gelling process of preparing aluminum hydroxide by carbonization method. The preparation method of the catalyst is to adopt a complete kneading method, that is, the aluminum hydroxide dry gel powder into which Ti is introduced by dripping titanium salt solution and the like is first added with an alkaline solution containing Mo and / or W, fully kneaded until the aluminum hydroxide powder is completely wetted by the alkaline liquid, and then an acidic solution containing Co and / or Ni is added, kneaded until the material becomes a plastic body, extruded into strips, dried, and roasted to obtain a catalyst. The method first contacts the alkaline solution containing the active component of group VIB with pseudo-boehmite, and then introduces the acidic solution containing the active component of group VIII into the above mixture for kneading and molding. Because the two types of active components are kneaded in steps, the bimetallic synergistic effect is weakened, which is not conducive to the formation of the active phase of the catalyst Co(Ni)-Mo-S, especially the type II active phase, resulting in an insignificant improvement in the activity of the catalyst.

[0006] The catalyst involved in patent application CN101954282A is composed of at least two of molybdenum, nickel, zinc and copper composite metal oxides as active components, at least one of Si, Ti, Ca, Ce, Mg and P oxides as an auxiliary agent, and the balance is alumina. Based on the mass of the catalyst, the mass percentage of the active component is 5-15%, the mass percentage of the auxiliary oxide is 0.2-25%, and the balance is alumina. The preparation method is to weigh at least two molybdenum, nickel, zinc and copper compounds respectively, mix them with at least one of silicon, titanium, calcium, cerium, magnesium and phosphorus compounds, and the other is aluminum compounds, add deionized water, mix them thoroughly, extrude them into strips, dry them in a blast drying oven, and roast them to obtain the target catalyst. This method prepares the catalyst by simply mechanically mixing the active components, auxiliary agents, alumina and water. On the one hand, there is no prefabricated metal solution, resulting in no synergistic effect between the active components of the catalyst and low hydrogenation activity; on the other hand, the selected metal nitrate is directly kneaded, which has safety hazards and is not universal in actual production. Summary of the invention

[0007] The present invention aims to provide a heavy fraction oil hydroprocessing catalyst and a preparation method thereof. The hydroprocessing catalyst prepared by the present invention has a larger pore volume and specific surface area, a concentrated pore size distribution, and is particularly suitable for a heavy oil fixed bed hydroprocessing process. The preparation method of the hydrogenation catalyst has the characteristics of simple process and low energy consumption, and is suitable for large-scale promotion and production.

[0008] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0009] One aspect of the present invention provides a method for preparing a heavy fraction oil hydroprocessing catalyst, the preparation method comprising:

[0010] An extrusion aid is added to the pseudo-boehmite, and the mixture is kneaded to obtain system 1;

[0011] The metal salt and / or metal oxide of the active component and the auxiliary agent are dissolved in deionized water to prepare a solution A with a pH of 6.5 to 7.5; the solution A is divided into a solution B and a solution C for standby use; a complexing agent is added to the solution C to obtain a solution D;

[0012] The solution B is added to the system 1, and kneaded until the pseudo-boehmite is completely soaked to obtain the precursor E; the solution D is added to the precursor E, and after kneading, the catalyst is obtained by molding, drying, and calcining.

[0013] The researchers of the present invention accidentally discovered through experiments that the activity of the hydrogenation catalyst prepared by the kneading method is closely related to the metal solution. In order to avoid the adverse effects on the catalyst activity caused by the acidic solution destroying the pore volume and specific surface of the alumina powder and the alkaline solution covering the acidic sites of the alumina in the prior art, the present invention adjusts the metal solution to a weak acid (base) or even neutral, which can retain the original pore structure of the alumina to the maximum extent. The preparation of the catalyst precursor is completed by adding and kneading twice; in this process, the volume of the above-mentioned solution B is determined according to the mass proportion of the active metal in the catalyst product. The main purpose is to use part of the metal in the solution B to contact the hydroxyl group of the pseudo-boehmite first to form a local pre-"occupancy". According to the characterization and final hydrogenation evaluation results, the optimal "occupancy" ratio is obtained, that is, the pore volume of the precursor E is reduced by 15% to 25% compared with the pore volume of the pseudo-boehmite; then the complex compounding technology is used to prepare the solution D, and the remaining metal complex is "anchored" on the vacant site of the precursor E, and the final catalyst product is obtained after subsequent drying and roasting.

[0014] According to the preparation method of the present invention, preferably, the specific surface area of ​​the pseudo-boehmite is 300m 2 / g~450m 2 / g, pore volume is 0.8cm 3 / g~1.3cm 3 / g, and the pores with a pore size distribution of 7nm to 15nm account for 60% to 95% of the total pores.

[0015] According to the preparation method of the present invention, preferably, the mass content of aluminum oxide in the pseudo-boehmite is 60wt% to 90wt%.

[0016] According to the preparation method of the present invention, preferably, the mass of the extrusion aid accounts for 1wt% to 5wt% of the mass of alumina in the pseudo-boehmite.

[0017] According to the preparation method of the present invention, preferably, the extrusion aid is selected from one or a combination of two or more of sesbania powder, methyl cellulose and starch.

[0018] According to the preparation method of the present invention, preferably, the kneading time after adding the extrusion aid to the pseudo-boehmite is 2 minutes to 30 minutes, preferably 5 minutes to 15 minutes.

[0019] According to the preparation method of the present invention, preferably, the metal element in the active component is selected from a combination of two or more elements in Group VIB and Group VIII.

[0020] According to the preparation method of the present invention, preferably, the metal element in the active component is selected from a combination of two or more of Mo, Co and Ni.

[0021] According to the preparation method of the present invention, preferably, the metal salt and metal oxide of the active component include molybdenum trioxide, ammonium molybdate, ammonium paramolybdate, cobalt nitrate, basic cobalt carbonate, cobalt chloride, nickel nitrate, basic nickel carbonate and nickel chloride.

[0022] According to the preparation method of the present invention, preferably, the ratio of solution B to solution A is 10v% to 50v%.

[0023] According to the preparation method of the present invention, preferably, when the active components are Mo and Ni, the ratio of solution B to solution A is 10v% to 30v%; when the active components are Mo, Ni and Co, the ratio of solution B to solution A is 30v% to 50v%.

[0024] According to the preparation method of the present invention, preferably, the auxiliary agent comprises one or a combination of two or more of phosphoric acid, diammonium phosphate, ammonium metaphosphate and ammonia water. The amount of the auxiliary agent added is based on the amount of P in the catalyst product. 2 O 5 The content can be determined.

[0025] According to the preparation method of the present invention, preferably, the complexing agent comprises one or a combination of two or more of citric acid, tartaric acid, ethylenediaminetetraacetic acid and glycerol.

[0026] According to the preparation method of the present invention, preferably, the mass of the complexing agent accounts for 1wt% to 15wt% of the mass of alumina in pseudo-boehmite; preferably 5wt% to 12wt%.

[0027] According to the preparation method of the present invention, preferably, ammonia water is used to adjust the pH of the solution A to 6.5-7.5.

[0028] According to the preparation method of the present invention, preferably, the solution D is added to the precursor E and kneaded for 10 min to 60 min; preferably 30 min to 45 min.

[0029] According to the preparation method of the present invention, preferably, the forming includes extrusion and tableting.

[0030] According to the preparation method of the present invention, preferably, the drying temperature is 80 to 150° C. and the drying time is 1 to 5 hours;

[0031] According to the preparation method of the present invention, preferably, the calcination temperature is 400-550° C. and the calcination time is 2 h-8 h.

[0032] Another aspect of the present invention provides a heavy fraction oil hydroprocessing catalyst obtained by the above preparation method.

[0033] According to the catalyst of the present invention, preferably, the composition of the catalyst comprises, by weight percentage: 10 wt% to 30 wt% of MoO 3 , 1wt% to 10wt% NiO, 1wt% to 10wt% CoO and 1wt% to 5wt% P 2 O 5 .

[0034] According to the catalyst of the present invention, preferably, the specific surface area of ​​the catalyst is 120 m 2 / g~250m 2 / g, pore volume is 0.3cm 3 / g~0.7cm 3 / g, and the average pore size is 4nm~20nm.

[0035] The hydroprocessing catalyst prepared by the invention has larger pore volume and specific surface area, concentrated pore size distribution, and is particularly suitable for heavy oil fixed bed hydroprocessing process.

[0036] The beneficial effects of the present invention include:

[0037] In the preparation method of the present invention, a weak acid (base) slightly neutral metal solution is first prepared to avoid the adverse effects of the prior art or acidic or alkaline solutions on the catalyst activity, and then the metal concentration and dispersion effect in the active component solution are increased through step-by-step complexation and compounding technology. Finally, a product with a higher pore volume and specific surface area is obtained through drying and roasting. The catalyst is more conducive to the completion of the diffusion-adsorption-reaction-desorption and other reaction processes of heavy oil macromolecules. DETAILED DESCRIPTION

[0038] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0039] All numerical specifications herein (e.g., temperature, time, concentration, and weight, etc., including ranges for each thereof) are generally approximate values ​​that may be appropriately varied (+) or (-) in increments of 0.1 or 1.0. All numerical specifications may be understood as being preceded by the term "about."

[0040] The macroporous pseudo-boehmite used in the following examples was produced by Shandong Binzhou Juxin Innovation Materials Co., Ltd. and has a specific surface area of ​​397 m 2 / g, pore volume is 1.1cm 3 / g, pores with a pore size distribution of 7-15 nm account for 88% of the total pores, the mass content of aluminum oxide is 72wt%, and other reagents are commercially available chemical reagents.

[0041] The present invention uses the ASAP 2405M specific surface and porosity analyzer of the American Micromeritics Instrument Company to measure the specific surface area and pore structure of the sample. The specific process is as follows: purify the sample under a vacuum degree of <104 mtorr; measure the surface N of the sample under different pressures at liquid nitrogen temperature. 2 The adsorption volume was determined by BET formula and the specific surface area of ​​the sample was calculated by BJH method.

[0042] Example 1

[0043] This embodiment adopts the preparation method of the present invention to prepare catalyst I, comprising the following steps:

[0044] (1) Take 200 g of macroporous pseudo-boehmite, add 6.0 g of sesbania powder, mix for 10 min, and set aside.

[0045] (2) Weigh 48.4 g of molybdenum trioxide (content 99 wt%), 15.7 g of basic nickel carbonate (nickel oxide content 51 wt%), and 6.5 g of phosphoric acid (concentration 85 wt%) respectively, heat to prepare 100 mL of aqueous solution, and then adjust the pH value to 7.0 with ammonia water to obtain solution A; divide solution A into solution B and solution C (wherein B:C=1:5 (V / V)), add 12.0 g of glycerol to solution C, mix well, and obtain solution D for use.

[0046] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst I. The physicochemical properties of the catalyst are shown in Table 1.

[0047] Example 2

[0048] This embodiment adopts the preparation method of the present invention to prepare catalyst II, comprising the following steps:

[0049] (1) Take 200 g of macroporous pseudo-boehmite, add 4.0 g of sesbania powder, mix for 10 min, and set aside.

[0050] (2) Weigh 48.4 g of molybdenum trioxide (content 99 wt%), 15.7 g of basic nickel carbonate (nickel oxide content 51 wt%), and 6.5 g of phosphoric acid (concentration 85 wt%) respectively, heat to prepare 100 mL of aqueous solution, and then adjust the pH value to 7.0 with ammonia water to obtain solution A; divide solution A into solution B and solution C (wherein B:C=1:4 (V / V)), add 12.0 g of glycerol to solution C, mix well, and obtain solution D for use.

[0051] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst II. The physicochemical properties of the catalyst are shown in Table 1.

[0052] Example 3

[0053] This embodiment adopts the preparation method of the present invention to prepare catalyst III, comprising the following steps:

[0054] (1) Take 200 g of macroporous pseudo-boehmite, add 2.0 g of sesbania powder, mix for 10 min, and set aside.

[0055] (2) Weigh 48.4 g of molybdenum trioxide (content 99 wt%), 15.7 g of basic nickel carbonate (nickel oxide content 51 wt%), and 6.5 g of phosphoric acid (concentration 85 wt%) respectively, heat to prepare 100 mL of aqueous solution, and then adjust the pH value to 7.0 with ammonia water to obtain solution A; divide solution A into solution B and solution C (wherein B:C=1:3 (V / V)), add 18.0 g of glycerol to solution C, mix well, and obtain solution D for use.

[0056] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst III. The physicochemical properties of the catalyst are shown in Table 1.

[0057] Example 4

[0058] This embodiment adopts the preparation method of the present invention to prepare catalyst IV, comprising the following steps:

[0059] (1) Take 200 g of macroporous pseudo-boehmite, add 3.0 g of starch, mix for 10 min, and set aside.

[0060] (2) Weigh 48.4 g of molybdenum trioxide (content 99 wt%), 15.7 g of basic nickel carbonate (nickel oxide content 51 wt%), and 6.5 g of phosphoric acid (concentration 85 wt%) respectively, heat to prepare 100 mL of aqueous solution, and then adjust the pH value to 7.0 with ammonia water to obtain solution A; divide solution A into solution B and solution C (wherein B:C=1:3 (V / V)), add 4.0 g of citric acid to solution C, mix well, and obtain solution D for use.

[0061] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst IV. The physicochemical properties of the catalyst are shown in Table 1.

[0062] Example 5

[0063] This embodiment adopts the preparation method of the present invention to prepare catalyst V, comprising the following steps:

[0064] (1) Take 200 g of macroporous pseudo-boehmite, add 6.0 g of sesbania powder, mix for 10 min, and set aside.

[0065] (2) Weigh 55.7 g of ammonium molybdate (with a molybdenum trioxide content of 86 wt%), 22.0 g of nickel nitrate (with a nickel oxide content of 25 wt%), and 6.5 g of phosphoric acid (with a concentration of 85 wt%), respectively, and prepare 100 mL of an aqueous solution, then adjust the pH value to 7.0 with aqueous ammonia to obtain a solution A; divide solution A into solution B and solution C (wherein B:C=1:3 (V / V)), add 8.0 g of tartaric acid to solution C, mix well, and obtain a solution D for use.

[0066] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst V. The physicochemical properties of the catalyst are shown in Table 1.

[0067] Example 6

[0068] This embodiment adopts the preparation method of the present invention to prepare catalyst VI, comprising the following steps:

[0069] (1) Take 200 g of macroporous pseudo-boehmite, add 6.0 g of sesbania powder, mix for 10 min, and set aside.

[0070] (2) Weigh 29.5 g of molybdenum trioxide (content 99 wt%), 10.8 g of basic nickel carbonate (nickel oxide content 51 wt%), 5.4 g of basic cobalt carbonate (cobalt oxide content 56 wt%), and 7.5 g of phosphoric acid (concentration 85 wt%) respectively, heat to prepare 100 mL of aqueous solution, and then adjust the pH value to 7.0 with ammonia water to obtain solution A; divide solution A into solution B and solution C (wherein B:C=3:7 (V / V)), add 12.0 g of glycerol to solution C, mix well, and obtain solution D for use.

[0071] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst VI. The physicochemical properties of the catalyst are shown in Table 1.

[0072] Example 7

[0073] This example uses the preparation method of the present invention to prepare catalyst VII, comprising the following steps:

[0074] (1) Take 200 g of macroporous pseudo-boehmite, add 6.0 g of sesbania powder, mix for 10 min, and set aside.

[0075] (2) Weigh 34.0 g of ammonium molybdate (with a molybdenum trioxide content of 86 wt%), 22.0 g of nickel nitrate (with a nickel oxide content of 25 wt%), 11.9 g of cobalt nitrate (with a cobalt oxide content of 25.5 wt%), and 7.5 g of phosphoric acid (with a concentration of 85 wt%), respectively, and heat to prepare 100 mL of an aqueous solution, and then adjust the pH value to 7.0 with aqueous ammonia to obtain a solution A; divide solution A into solution B and solution C (wherein B:C=2:3 (V / V)), add 12.0 g of glycerol to solution C, mix well, and obtain a solution D for use.

[0076] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst VII. The physicochemical properties of the catalyst are shown in Table 1.

[0077] Example 8

[0078] This embodiment adopts the preparation method of the present invention to prepare catalyst VIII, comprising the following steps:

[0079] (1) Take 200 g of macroporous pseudo-boehmite, add 6.0 g of methyl cellulose (viscosity: 400 mPa·s), mix for 10 min, and set aside.

[0080] (2) Weigh 29.5 g of molybdenum trioxide (content 99 wt%), 10.8 g of basic nickel carbonate (nickel oxide content 51 wt%), 5.4 g of basic cobalt carbonate (cobalt oxide content 56 wt%), and 7.5 g of phosphoric acid (concentration 85 wt%) respectively, heat to prepare 100 mL of aqueous solution, and then adjust the pH value to 7.0 with ammonia water to obtain solution A; divide solution A into solution B and solution C (wherein B:C=2:3 (V / V)), add 12.0 g of glycerol to solution C, mix well, and obtain solution D for use.

[0081] (3) Solution B is directly added to the system obtained in (1), and kneaded until the pseudo-boehmite is completely infiltrated to obtain precursor E; then solution D is slowly added to E, and kneaded for 40 minutes until it becomes a plastic body, and then extruded into strips on a forward extrusion twin-screw extruder. The clover strips were dried at 120°C for 3 h and calcined at 480°C for 4 h to obtain hydrogenation catalyst VIII. The physicochemical properties of the catalyst are shown in Table 1.

[0082] Comparative Example 1

[0083] This comparative example adopts the following steps to prepare catalyst IX:

[0084] (1) Take 200g of macroporous pseudo-boehmite, add 6.0g of sesbania powder, 6.0g of citric acid, 7.5g of nitric acid (concentration 65.0wt%), and an appropriate amount of deionized water, mix and knead until a plastic body is obtained, and then extrude into strips on a front extrusion twin-screw extruder. The clover strips were dried at 100°C for 2 h and calcined at 550°C for 4 h to obtain a catalyst carrier;

[0085] (2) Weighing 48.4 g of molybdenum trioxide (content 99 wt%), 15.7 g of basic nickel carbonate (nickel oxide content 51 wt%), and 6.5 g of phosphoric acid (concentration 85 wt%), respectively, and heating to prepare 100 mL of active metal aqueous solution;

[0086] (3) The support of (1) was impregnated with the solution of (2), cured at room temperature for 8 h, dried at 120° C. for 3 h, and calcined at 480° C. for 4 h to obtain hydrogenation catalyst IX. The physicochemical properties of the catalyst are shown in Table 1.

[0087] Comparative Example 2

[0088] This comparative example adopts the following steps to prepare catalyst X:

[0089] Weigh 200g of macroporous pseudo-boehmite, add 140g of ammonium molybdate solution, where MoO3 Concentration 30.0wt%, solution contains NH 3 The mixture is 10 wt % and fully mixed until the alkali solution wets the aluminum hydroxide powder. Then 144 g of acid solution is added. The acid solution contains Ni(NO 3 ) 2 :16.2wt%Co(NO 3 ) 2 : 16.2wt%, the solution contains 17wt% acetic acid, fully kneaded to a plastic body, and then extruded into strips on a front extrusion twin-screw extruder The catalyst was dried at 100°C for 4 hours and calcined at 490°C for 3 hours to obtain catalyst X. The physicochemical properties of the catalyst are shown in Table 1.

[0090] Table 1 Catalyst physicochemical properties

[0091]

[0092] From the analysis results in Table 1, it can be seen that the Mo-Ni hydrogenation catalyst prepared by the impregnation method in Comparative Example 1 is 176m 2 / g, pore volume 0.37cm 3 / g, average pore size 7.9nm, compared with Example 1, specific surface area, pore volume and average pore size were reduced by 42m 2 / g, 0.1cm 3 / g and 1.2nm. This is mainly due to the introduction of a highly acidic adhesive (nitric acid), which has a certain impact on the pore structure of pseudo-boehmite, thereby causing a decrease in catalyst activity. Comparative Example 2 uses a kneading method to prepare a Co-Mo-Ni hydrogenation catalyst. Although the agent has a large specific surface area, pore volume and pore size, the method of first adding an alkaline solution containing Mo to wet it and then adding an acidic solution containing Ni and Co to knead it will cause the active phase of the catalyst Co(Ni)MoS, especially the II active phase, to decrease or be missing, resulting in a relatively low catalyst activity.

[0093] Example 9

[0094] This example is a catalyst activity evaluation test, that is, on a 200mL small hydrogenation evaluation device, the catalysts of Examples 1 to 8 and Comparative Examples 1 to 2 were first sulfurized, and then the same process conditions were used: reaction pressure 12.0MPa, reaction temperature 360°C, hydrogen-to-oil ratio 650:1 and volume space velocity 1.0h -1 , mixed wax oil raw materials were treated, and the performances of hydrodesulfurization (HDS), hydrodenitrogenation (HDN) and hydrodecarbon residue (HDCCR) were investigated. The properties of the raw oil and the properties of the hydrogenated products are shown in Tables 2 and 3.

[0095] Table 2 Raw oil properties

[0096] project Mixed wax oil <![CDATA[Density, g / cm 3 > 0.9223 Sulfur content, μg / g 15760 Nitrogen content, μg / g 1810 Residual carbon content, wt% 1.18

[0097] Table 3 Properties of hydrogenation products

[0098]

[0099] From the evaluation results in Table 3, under the same working conditions, the catalyst prepared in Comparative Example 1 was used to treat the same wax oil raw material, and its HDS: 94.2%, HDN: 71.5%, HDMCR: 85.1%, which was 3.0 percentage points lower than the catalyst prepared in Example 1, 5.6 percentage points lower than the HDMCR, and 6.1 percentage points lower than the catalyst prepared in Example 1. The catalyst prepared in Comparative Example 2 had HDS: 93.7%, HDN: 67.4%, HDMCR: 81.5%, which was 3.0 percentage points lower than the catalyst prepared in Example VII, 9.1 percentage points lower than the HDMCR, and 7.4 percentage points lower than the catalyst prepared in Example VII. This shows that the catalyst prepared by the method of the present invention has higher hydrogenation activity.

[0100] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a heavy distillate oil hydrotreating catalyst, characterized in that: The preparation method comprises: An extrusion aid is added to the pseudo-boehmite, and the mixture is kneaded to obtain system 1; The metal salt and / or metal oxide of the active component and the auxiliary agent are dissolved in water to prepare a solution A with a pH of 6.5 to 7.5; the solution A is divided into a solution B and a solution C for standby use; a complexing agent is added to the solution C to obtain a solution D; The solution B is added into the system 1, so that part of the metal in the solution B first contacts the hydroxyl group of the pseudo-boehmite to form a pre-occupied position locally, and the precursor E is obtained after the pseudo-boehmite is completely infiltrated by mixing and kneading. The occupation ratio is controlled so that the pore volume of the precursor E is reduced by 15% to 25% compared with the pore volume of pseudo-boehmite; The solution D is added to the precursor E, so that the remaining metal complex is anchored on the vacant position of the precursor E, and after kneading, the catalyst is obtained by molding, drying and calcining; The metal element in the active component is selected from a combination of two or more of Mo, Co and Ni; The ratio of solution B to solution A is 10v% to 50v%; When the active components are Mo and Ni, the ratio of solution B to solution A is 10v% to 30v%; when the active components are Mo, Ni and Co, the ratio of solution B to solution A is 30v% to 50v%; The auxiliary agent includes one or a combination of two or more of phosphoric acid, ammonium metaphosphate and ammonia water.

2. The preparation method according to claim 1, characterized in that: The specific surface area of ​​the pseudo-boehmite is 300m 2 / g~450m 2 / g, pore volume is 0.8cm 3 / g~1.3cm 3 / g, and the pores with a pore size distribution of 7nm to 15nm account for 60% to 95% of the total pores.

3. The preparation method according to claim 2, characterized in that: The mass content of aluminum oxide in the pseudo-boehmite is 60wt% to 90wt%.

4. The preparation method according to claim 3, characterized in that: The mass of the extrusion aid accounts for 1wt% to 5wt% of the mass of alumina in pseudo-boehmite.

5. The preparation method according to claim 1, characterized in that: The extrusion aid is selected from one or a combination of two or more of sesbania powder, methyl cellulose and starch.

6. The preparation method according to claim 1, characterized in that: The metal salts and metal oxides of the active components include molybdenum trioxide, ammonium molybdate, ammonium paramolybdate, cobalt nitrate, basic cobalt carbonate, nickel nitrate and basic nickel carbonate.

7. The preparation method according to claim 1, characterized in that: The complexing agent includes one or a combination of two or more of citric acid, tartaric acid, ethylenediaminetetraacetic acid and glycerol.

8. The preparation method according to claim 1, characterized in that: The mass of the complexing agent accounts for 1wt% to 15wt% of the mass of alumina in pseudo-boehmite.

9. A heavy distillate oil hydrotreating catalyst obtained by the preparation method according to any one of claims 1 to 8.

10. The heavy distillate oil hydroprocessing catalyst according to claim 9, characterized in that: The composition of the catalyst includes, by weight percentage: 10wt% to 30wt% of MoO3, 1wt% to 10wt% of NiO, 1wt% to 10wt% of CoO and 1wt% to 5wt% of P2O5.

11. The heavy distillate oil hydroprocessing catalyst according to claim 9, characterized in that: The specific surface area of ​​the catalyst is 120 m 2 / g~250m 2 / g, pore volume is 0.3cm 3 / g~0.7cm 3 / g, and the average pore size is 4nm~20nm.

Citation Information

Patent Citations

  • Preparation method of hydrocarbon hydrotreatment catalyst

    CN100340638C

  • Hydrodesulphurization catalyst and preparation method thereof

    CN101954282A

  • Highly stable hydroprocessing catalyst

    US4443558A

  • Heavy oil hydrogenating treatment catalyst and preparation method thereof

    CN101433848A

  • Method for preparing high-activity hydrogenation catalyst

    CN1253854A